In-vivo Activity of IFN-λ and IFN-α Against Bovine-Viral-Diarrhea Virus in a Mouse Model - Quintana, María Eugenia; Barone, Lucas José; Trotta, Myrian Vanesa; Turco, Cecilia; Mansilla, Florencia Celeste; Capozzo, Alejandra Victoria; Cardoso, Nancy Patricia (Frontiers in Veterinary Science, 2020)
Bovine-viral-diarrhea virus (BVDV) can cause significant economic losses in livestock. The disease is controlled with vaccination and bovines are susceptible until vaccine immunity develops and may remain vulnerable if a persistently infected animal is left on the farm; therefore, an antiviral agent that reduces virus infectivity can be a useful tool in control programs. Although many compounds with promising in-vitro efficacy have been identified, the lack of laboratory-animal models limited their potential for further clinical development. Recently, we described the activity of type I and III interferons, IFN-α and IFN-λ respectively, against several BVDV strains in-vitro. In this study, we analyzed the in-vivo efficacy of both IFNs using a BALB/c-mouse model. Mice infected with two type-2 BVDV field strains developed a viremia with different kinetics, depending on the infecting strain's virulence, that persisted for 56 days post-infection (dpi). Mice infected with the low-virulence strain elicited high systemic TNF-α levels at 2 dpi. IFNs were first applied subcutaneously 1 day before or after infection. The two IFNs reduced viremia with different kinetics, depending on whether either one was applied before or after infection. In a second experiment, we increased the number of applications of both IFNs. All the treatments reduced viremia compared to untreated mice. The application of IFN-λ pre- and post-infection reduced viremia over time. This study is the first proof of the concept of the antiviral potency of IFN-λ against BVDV in-vivo, thus encouraging further trails for a potential use of this cytokine in cattle.